The Supply Chain Management on Customer Bonding towards Customer Relationship Management in Mediating Dominant of Customer Value in the Village Credit Institution of Bali Province, Indonesia - Sadiartha, Anak Agung Ngurah Gede (ExcelingTech, 2020)
Nowadays, business competition is very competitive, like in financial services business, including banks, Village Credit Institution and other financial service business must always try to meet customer satisfaction. From empirical test result, it is obtained that significance level of research for customer value variable significantly impactd customer retention of 0,000 0.05, so H1 is accepted. Customer value has a significant impact on customer retention in the Village Credit Institution. From the empirical test result, it is obtained that significance level of customer value on Customer relationship management is 0,000 0.05, so H2 is accepted. The customer value significantly impacts Customer relationship management in the Village Credit Institution. From empirical test, it is obtained the level of research significance for the variable Customer relationship management to customer retention of 0.023 0.05, so H3 is accepted. Customer relationship management has a significant impact on customer retention in the in the Village Credit Institution. From empirical test, it is obtained that the Zcount (30.8) Z table (1.96) so Customer relationship management can mediate the relationship between customer value and customer retention. Thus, H4 is accepted